Peningkatan Keterampilan Menulis Puisi Menggunakan Model Pembelajaran Brain Writing di Kelas IV SDN 21 Taluak IV Suku Kabupaten Agam - Asyifa, Nazla; Suriani, Ari; Sukma, Elfia; Muhammadi, Muhammadi (Darul Yasin Al Sys, 2025)
This research is motivated by the low interest of students in writing skills, which is caused by: 1) students not understanding diction and language style in poetry writing activities, 2) students being unable to express their ideas through writing, so they rely on poems written or recited by the teacher, 3) difficulty in expressing ideas, usually due to students not knowing what to write or where to start writing the various ideas in their minds, 4) difficulty in constructing words or sentences correctly, which makes students feel that their writing does not meet expectations, leading to attempts to replace sentences, and 5) in poetry writing, where the teacher reads aloud, students have not used typography for aesthetic writing of the poem.